Implementation of Specific Nutrition Interventions to Prevent Stunting in Pregnant Women in the Oesapa Community Health Center Area East Nusa Tenggara - Katmawanti, Septa; Wahyuni, Oktavia Sri; Paramita, Farah; Kurniawan, Agung; Khuzaimah, Siti (Preventia: The Indonesian Journal of Public Health, 2024)
Policies related to stunting prevention have been in place since 2013. However, the prevalence of stunting in East Nusa Tenggara Province is still the highest in Indonesia from 2013 to 2022. One of the areas in the province where the prevalence decreased from 2021 to 2022 is Kupang City. Oesapa Community Health Centre was appointed by the Indonesian Ministry of Health as a pilot health centre representing Kupang City. The purpose of this study is to describe the implementation of specific nutritional interventions for handling stunting based on the variables of communication, bureaucratic structure, resources, and disposition in the target group of pregnant women which will be associated with the target achievement of specific nutritional interventions based on Presidential Regulation No 72 of 2021. The research used qualitative methods with triangulation of informants totalling 5 people, data triangulation, and triangulation of methods, namely in-depth interviews and observations. The results showed that interventions in the form of providing additional food to pregnant women with chronic energy deficiency conditions and pregnant women who consume blood supplement tablets at least 90 tablets during pregnancy have successfully reached the target. Other Community Health Centres can make the Oesapa Community Health Centre a barometer in providing health services, especially in specific nutrition interventions aimed at target groups of pregnant women so that they work together in accelerating the reduction in stunting prevalence.